Association between behavioral and psychological symptoms and cerebral small vessel disease MRI findings in memory clinic patients - Shinohara, Masaki; Matsuda, Kana; Ii, Yuichiro; Tabei, Ken-ichi; Nakamura, Naoko; Hirata, Yoshinori; Ishikawa, Hidehiro; Matsuyama, Hirofumi; Matsuura, Keita; Maeda, Masayuki; Tomimoto, Hidekazu; Shindo, Akihiro (Frontiers in Aging Neuroscience, 2023)
Objectives Cerebral small vessel disease (SVD) is commonly observed among elderly individuals with cognitive impairment and has been recognized as a vascular contributor to dementia and behavioral and psychological symptoms (BPS), however, the relationship between BPS and SVD burden remains unclear. Methods We prospectively recruited 42 patients with mild cognitive impairment (MCI) or mild dementia from the memory clinic in our hospital, who were assigned to either a clinical dementia rating (CDR) of 0.5 or 1.0, respectively. The presence of BPS was determined through interviews with caregivers. The patients underwent brain MRI and three types of SVD scores, total, cerebral amyloid angiopathy (CAA), and modified CAA, were assigned. Patients were also evaluated through various neuropsychological assessments. Results The CDR was significantly higher in patients with BPS (p = 0.001). The use of antihypertensive agents was significantly higher in patients without BPS (p = 0.038). The time taken to complete trail making test set-A was also significantly longer in patients with BPS (p = 0.037). There was no significant difference in total SVD and CAA-SVD score (p = 0.745, and 0.096) and the modified CAA-SVD score was significantly higher in patients with BPS (p = 0.046). In addition, the number of total CMBs and lobar CMBs was significantly higher in patients with BPS (p = 0.001 and 0.001). Receiver operating characteristic curves for BPS showed that for modified CAA-SVD, a cutoff score of 3.5 showed 46.7% sensitivity and 81.5% specificity. Meanwhile, for the total number of cerebral microbleeds (CMBs), a cut-off score of 2.5 showed 80.0% sensitivity and 77.8% specificity and for the number of lobar CMBs, a cut-off score of 2.5 showed 73.3% sensitivity and 77.8% specificity. Conclusion Overall, patients with BPS showed worse CDRs, reduced psychomotor speed, higher modified CAA-SVD scores, larger numbers of total and lobar CMBs. We propose that severe modified CAA scores and higher numbers of total and lobar CMBs are potential risk factors for BPS in patients with mild dementia or MCI. Therefore, by preventing these MRI lesions, the risk of BPS may be mitigated.